Microglia and programmed cell death in spinal cord injury: beyond apoptosis - Huang, Ming; Yao, Guoquan; He, Baowen; Zhou, Xiaohu; Liu, Guoqing; Dong, Wenfei (Frontiers in Cell and Developmental Biology, 2025)
Spinal cord injury (SCI) triggers a multifaceted cascade of cellular and molecular events that profoundly influence the extent of secondary damage. Central to this process, microglia—the innate immune cells of the central nervous system—display a range of programmed cell death pathways that have significant implications for injury outcomes. This article mainly focuses on three key programmed cell death modalities that have emerged in SCI: ferroptosis, autophagy, and pyroptosis. Ferroptosis, characterized by iron-dependent lipid peroxidation, autophagy, which can serve dual roles in cell survival and death, and pyroptosis, an inflammatory form of cell death, contribute uniquely to the progression and resolution of post-injury neuroinflammation. We examine the underlying molecular mechanisms, the regulatory networks that integrate these pathways, and how their dysregulation may exacerbate tissue damage. Moreover, potential therapeutic strategies to modulate these specific cell death processes are discussed, offering promising avenues for reducing secondary damage and enhancing recovery in patients with SCI.